2009
DOI: 10.1245/s10434-008-0267-6
|View full text |Cite
|
Sign up to set email alerts
|

Blood Neutrophil-to-Lymphocyte Ratio Predicts Survival in Patients with Colorectal Liver Metastases Treated with Systemic Chemotherapy

Abstract: NLR independently predicts survival in patients with CLM treated with chemotherapy followed by resection or chemotherapy only. When chemotherapy normalizes high NLR, improved survival is expected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
249
2
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 309 publications
(264 citation statements)
references
References 27 publications
10
249
2
3
Order By: Relevance
“…Previous reports indicated a significant correlation between the neutrophil count or neutrophil-lymphocyte ratio and survival in a variety of clinical settings including gastric cancer (Yamanaka et al, 2007;Kishi et al, 2009;Jung et al, 2011;Dalpiaz et al, 2013;Fox et al, 2013;Lee et al, 2013;Sugiura et al, 2013). However, in the present study, we found that only elevated neutrophil count was an independent predictor of poor survival in multivariate analysis.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Previous reports indicated a significant correlation between the neutrophil count or neutrophil-lymphocyte ratio and survival in a variety of clinical settings including gastric cancer (Yamanaka et al, 2007;Kishi et al, 2009;Jung et al, 2011;Dalpiaz et al, 2013;Fox et al, 2013;Lee et al, 2013;Sugiura et al, 2013). However, in the present study, we found that only elevated neutrophil count was an independent predictor of poor survival in multivariate analysis.…”
Section: Discussioncontrasting
confidence: 95%
“…Several recent studies have revealed a correlation between clinical outcomes with common solid tumors (colorectal cancer, lung cancer, breast cancer and pancreatic cancer, etc) and systemic inflammatory response, including plasma C-reactive protein (CRP), hypoalbuminemia, and a selective combination of C-reactive protein and albumin termed as Glasgow Prognostic Score (GPS) (Leitch et al, 2007;Hwang et al, 2011;Jiang et al, 2012;Fox et al, 2013;McMillan, 2013). There were also many studies reporting that haematological markers of systemic inflammatory response such as white blood cell count or its components (neutrophil, lymphocyte, neutrophil-lymphocyte ratio (NLR)), platelet, and platelet-lymphocyte ratio (PLR) are also prognostic indicators for cancer clinical outcomes (Yamanaka et al, 2007;Cho et al, 2009;Kishi et al, 2009;Sarraf et al, 2009;Kwon et al, 2012;Dalpiaz et al, 2013;Fox et al, 2013). In addition, other inflammatory factor combinations such as Prognostic Index (PI) and Prognostic Nutritional Index (PNI) have also been linked with prognosis of malignancies (Kasymjanova et al, 2010;Nozoe et al, 2010;Kanda et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Halazun et al (2008) found that elevated NLR increases both risk of death and the risk of recurrence in patients who undergo surgery for CRC liver metastases. Furthermore Kishi et al (2009) reported that NLR independently predicts survival in patients with liver metastasis of CRC treated with chemotherapy followed by resection or chemotherapy alone. Nonetheless, all of these studies emphasize that NLR has prognostic significance in cancer patients in terms of survival.…”
Section: Discussionmentioning
confidence: 99%
“…Authors suggested that NLR could be an important marker to monitor early response to chemotherapy and prognosis. It was reported that increase in PLR (>150) was an independent risk factor for increasing mortality in patients with colorectal or pancreas cancer (Kishi et al, 2009;Smith et al, 2009;Kwon et al, 2012).…”
Section: Discussionmentioning
confidence: 99%